Geriatric Health Care through Rasayana : A Review - Ansari, Md Tanzil; Ghosh , Sukumar; Talapatra, Trisha (International Research Journal of Ayurveda & Yoga, 2020)
Jara (Ageing) is the natural phenomenon. Hence old age is unavoidable. During Vriddhavastha, there is predominance of Vata dosha which accelerates the process of ageing. On the other hand there is deterioration of Rasadi dhatus which in turn affects the general health of aged people. So, proper health care is very much needed during this phase of life. In Ayurveda Jara chikitsa (also known as Rasayana chikitsa) is meant for geriatric health care. Rasayana is one of the best vayasthapak (prevents ageing) and complete health care measures for aged people. Acharya Sushruta has described it as the methods of withholding ageing, increasing life span, intelligence, strength and capacity to get rid of diseases. It prevents Akalaja jara (premature ageing) and delays Kalaja jara (natural ageing). Geriatric health care can be provided by age specific, disease specific, dhatu specific, medhya and achara rasayana. Hence rasayana provides physical, mental and social support to aged person. This article is based on the review of Geriatric health care through Rasayana.